Ultrasound-Assisted Lipid Extraction of Chlorella sp. for Biodiesel Production: Optimization Study - Yheni Mulyaningsih; Aditya Harjon Bahar; Fazril Ideris; Rico Aditia Prahmana (Politeknik Negeri Medan, 2026)
Microalgae are a promising third-generation biofuel feedstock due to their high lipid and carbohydrate content. In this study, Chlorella pyrenoidosa biomass was subjected to alkaline hydrolysis to release fermentable substrates, and the process was optimized using a Box–Behnken response surface methodology. The key parameters – microalgal concentration, NaOH concentration, temperature, and hydrolysis time – were varied to maximize reducing sugar yield. The experimental data were fitted to a statistical model (R²>0.99), which identified significant positive effects of higher biomass loading and longer hydrolysis time on sugar release. Under the optimal conditions, the model predicts a maximum sugar concentration (approximately 0.47–0.50 g/L) from the hydrolysate. These results demonstrate the feasibility of converting Chlorella biomass into biofuel precursors. The findings are discussed in relation to biodiesel production strategies: for example, ultrasound-assisted extraction methods have achieved 18.8% lipid yield from Chlorella under optimized conditions. Future work should integrate ultrasound pretreatment and lipid recovery (e.g. direct transesterification) to fully exploit microalgal biofuel potential.